Meningkatkan Kemampuan Muraja’ah Tahfidz Al-Qur’an Perspektif Metode Talaqqi - Izzan, Ahmad; Fadhil, Sahrul (MASAGI : Jurnal Pendidikan Agama Islam, 2023)
The Qur'an was revealed by Allah SWT as proof of the truth of Prophet Muhammad SAW, with its primary function being guidance for humankind. The Qur'an narrates many aspects of education and its urgency for human life. The ability of muraja'ah in the Qur'an is one of the methods to consistently remember our memorization or preserve and maintain the fluency of Qur'anic memorization, ensuring that the Qur'anic memorization achieved through hard work does not fade away. The Talaqqi method is a teaching method of the Qur'an by directly imitating the recitation of the teacher and then mimicking the demonstration of the teacher. This research aims to answer several research questions: 1) to describe the concept of the Talaqqi method in Qur'anic memorization, 2) to describe the ability of muraja'ah in the Qur'an, and 3) to describe the ability of muraja'ah in Qur'anic memorization from the perspective of the Talaqqi method. This study employs library research as its type, utilizing qualitative research methods. Data sources consist of primary sources such as Talaqqi books, and secondary sources including books, journals, and other relevant readings supporting this research. The results of this study indicate that the ability of muraja'ah in Qur'anic memorization from the perspective of the Talaqqi method emphasizes repetitive learning methods aimed at consistently remembering or preserving and maintaining the fluency of Qur'anic memorization effectively. Therefore, Qur'anic learning using the Talaqqi method ensures that memorized Qur'anic verses do not easily fade from memory, emphasizing the importance of regular revision to maintain memorization. These findings contribute to the scholarly understanding of effective Qur'anic learning methods.  Keywords: Qur'an, Talaqqi Method, Muraja'ah